Engaging Civil Society Organizations in Conflict-Affected and Fragile States : Three African Country Case Studies - World Bank (Washington, DC, 2012)
Civil society organizations (CSOs) play a prominent role in conflict-affected and fragile states. In the absence of capable or credible public institutions due to conflict or weak policy environments, CSOs tend to substitute for public institutions and become primary providers of basic social services. At the same time, the international donor community has increased its involvement in countries affected by conflict and instability, often relying increasingly on CSOs to reach the poor. While the prominent role of CSOs in social service delivery and other development activities is often seen as an interim solution, it may extend for years, even decades. Recognizing that reliance on CSOs is likely to prevail for the foreseeable future in many countries, there is a need to consider how to make CSO engagement more effective and sustainable. The objective of this report is to identify approaches to more effectively engage CSOs in the context of weak public institutions in conflict-affected and fragile states. The report will: 1) Examine the roles, strengths, and weaknesses of CSOs in terms of service delivery, community development, advocacy, peace building, and governance; 2) Identify the factors that influence CSO effectiveness in performing these functions; 3) Assess donor influence on CSOs and their indirect influence on governance by supporting CSOs; and 4) Discuss the relationship between CSOs and government including their changing roles, weak communication, and government efforts to coordinate and regulate CSO activity. Key findings are presented from pilots of the Civil Society Assessment Tool (CSAT) in Angola, Guinea Bissau, and Togo. The pilots were carried out from January 2004 to February 2005.